Standard diagnostic laparoscopy is superior to NOTES approaches: results of a blinded, randomized controlled porcine study - Renteln, Daniel Alexander Patrick von; Gutmann, Tamara Esther; Schmidt, Arthur; Vassiliou, M. C.; Rudolph, Hans Ulrich; Caca, Karel (Endoscopy, 2012)
Background and study aim: The use of transluminal endoscopic access via the stomach or colon for flexible diagnostic peritoneoscopy has been proposed, although the diagnostic value of the technique has not yet been fully clarified. In this animal trial, the two main natural orifice transluminal endoscopic surgery (NOTES) approaches - transgastric (TG) and transcolonic (TC) - were compared with standard transabdominal access using both rigid (TAR) and flexible instruments (TAF) for diagnostic laparoscopy.Methods: A total of 48 peritoneoscopies were performed using two randomly assigned approaches in 24 anesthetized pigs. The ability of the examinations to detect 576 electrocautery markings simulating intraperitoneal metastases, to achieve complete organ visualization, and to simulate organ biopsies was analyzed.Results: Sensitivities for the detection of lesions were 78.5 %, 59.7 %, 48.6 %, and 38.9 % for TAR, TAF, TC, and TG, respectively; standard laparoscopy was superior to all other approaches (P < 0.01). Among the NOTES approaches, TC was superior for examining the upper abdomen (P = 0.03). Complete organ visualization was better with the transabdominal approach (visual analogue scale TAR 7.15, TAF 6.71) than with the NOTES access routes (TC 5.07, TG 4.35); standard rigid laparoscopy was superior to both NOTES approaches (P < 0.01). Organ biopsy simulation was possible in 87 %, 85 %, 72 %, and 65 % of cases with TAR, TAF, TC, and TG, respectively. Standard rigid laparoscopy was again superior to both NOTES approaches (TAR vs. TC, = 0.03; TAR vs. TG, < 0.01). Conclusions: In this experimental trial, rigid standard laparoscopy provided better organ visualization, better lesion detection, and better biopsy capability than the transgastric and transcolonic NOTES approaches. In its current form, NOTES appears to be unsuitable for diagnostic laparoscopy.
Publikationsdatum: 08. März 2012 (eFirst)
Gesehen am 11.11.2024